Effectiveness of Clean and Healthy Living Behavior (CHLB) Counseling for Community Empowerment and Environmental Health Improvement: Evidence from Malang City - Okrofa, Melania; Anggarani, Dwi; Ainun, Siti Nur; Baits Nur, Ayu Wandani Mustika Rahma (Badan Perencanaan Pembangunan Kota Malang, 2025)
Improving public health is a priority in urban development strategies, including in Malang City. This study evaluates the effectiveness of Clean and Healthy Living Behavior (CHLB) counseling as a community empowerment intervention to enhance knowledge, attitudes, and practices of local residents. A descriptive qualitative approach was employed, using observations, in-depth interviews, and focus group discussions (FGDs) involving 60 households and primary school students in Lowokwaru District, Malang City. The findings reveal a significant improvement in handwashing practices, proper latrine use, and household waste management. Moreover, community participation in collective environmental activities increased, contributing to a cleaner neighborhood and a reduction in environmentally related diseases. At the school level, students displayed strong enthusiasm and incorporated healthy habits into their daily routines. These behavioral changes also generated socioeconomic benefits, including reduced household health expenditures. The results provide empirical evidence that CHLB counseling is an effective community empowerment strategy for improving public health and environmental quality. Scaling up similar programs with strong support from local government, educational institutions, and active community participation is recommended to transform CHLB into a sustainable lifestyle.